Better off alone? Compared performance of monoclonal and polyclonal stands of a cultivated red alga growth. (22nd January 2020) - Usandizaga, Sara; Buschmann, Alejandro H.; Camus, Carolina; Kappes, José Luis; Arnaud‐Haond, Sophie; Mauger, Stéphane; Valero, Myriam; Guillemin, Marie Laure
Abstract: The objective of this study was to test, using a field experiment, the effect of genotypic diversity on productivity of farmed populations (Ancud and Chaica, Chile) of the domesticated red alga Agarophyton chilense (formerly known as Gracilaria chilensis ), a species considered as economically important in Chile. Monoclonal and polyclonal (4 and 8 genotypes) subplots were outplanted into the mid intertidal in Metri Bay (Puerto Montt, Chile) during summer, a season in which A. chilense face higher temperatures (>18°C) and low nitrogen availability (<4.00 μmol). Ancud farm genotypes show higher growth rates in the monoclonal rather than the two polyclonal subplots. A similar tendency, yet not significant, was discernible in Chaica. In addition, whatever the population of origin of the thalli, no effect of genotypic diversity was detected neither on the agar yield and its quality, nor on the epiphyte load. Such unexpected results of a higher performance in plots with a lower genotypic diversity could be explained (a) by human‐assisted selection for dominant‐best‐performing genotypes that could counterbalance the negative effect caused by the low genotypic diversity in farms and (b) by the fact that the organisms inhabiting the algal mats do not impact the fitness of their host. Overall, the results obtained here suggest that despite farm induced selection lead to impoverished pools of genotypes, they may also have a positive effect of on the resistance of farmed populations to seasonal stressors. However, whether this may have a secondary negative effect on the longer term in a fluctuating environment remains to be determined, but may be avoided by adopting strategy of selection favoring different genotypes in space and time, as implemented in forestry.